PENGARUH MARKET TIMING TERHADAP LEVERAGE PADA PERUSAHAAN NONKEUANGAN YANG MELAKUKAN INITIAL PUBLIC OFFERING DI BURSA EFEK INDONESIA - Indah Karmila; Said Musnadi (Departemen Manajemen, 2020)
This study aims to examine the effects of market timing and its persistence on changes in the level of leverage in non-financial companies which conduct IPOs on the Indonesia Stock Exchange for the 2009-2017 period. The purposive sampling technique with certain criteria was used in the study to obtain a sample of 87 companies in each IPO period. The Ordinary Least Squares (OLS) method was used for the analysis.The results indicate that the market to book ratio has significant negative effects on the level of change in leverage and the market timing has long-term effects (persistence) on the companies leverage until the time of study t+3. The results of this study are expected to be a consideration for companies to be able to optimize the capital structure by looking at market conditions. For investors, this research is expected to help to analyze the phenomenon of market timing so that investors can determine the right time to sell and buy shares, thus investors can maximize investment returns.